Leadership in high performance organizational cultures - Truskie, Stanley D. (Quorum Books, 1999)
Against a background of continuing disagreement on what leadership is, Truskie offers his own concise concept by delineating leadership's two critical tasks: establishing organizational direction and developing organizational effectiveness. Truskie focuses mainly on the latter. He shows how leaders can help their organizations become effective and experience superior, long-term performance by developing an integrated, balanced organizational culture - using a method he calls the L[superscript 4] Strategy. He supports it with numerous real-world business situations from his personal research and consulting, plus examples and applications from other sources. With guidelines for leaders to follow in adapting themselves personally to this new leadership strategy. Dr.